2021
DOI: 10.1002/ldr.4109
|View full text |Cite
|
Sign up to set email alerts
|

A global meta‐analysis of the impacts of no‐tillage on soil aggregation and aggregate‐associated organic carbon

Abstract: No‐tillage (NT) has been shown to control soil degradation by impacting soil aggregates (i.e., basic units of soil structure, whose characteristics mediate key soil processes, like carbon sequestration). However, there has been no systematic analysis of the impacts of NT on soil aggregation and aggregate‐associated soil organic carbon (SOC) at global level. We conducted a global meta‐analysis of 89 publications to elucidate the changes in soil aggregation and aggregate‐associated SOC under NT. Notably, we quan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 55 publications
(27 citation statements)
references
References 99 publications
(157 reference statements)
1
18
0
Order By: Relevance
“…In this study, the highest N application rate (210 kg N ha −1 ) could induce toxicity, resulting in lesser microbial diversity. In addition, CT had lower soil SOC (Li et al, 2010; Liu et al, 2021) and C/N ratio compared with NT (Fiorini et al, 2020), which leads to carbon limiting for microorganisms. Hence, the effect of N application had a smaller effect on microbial diversity under CT than NT.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the highest N application rate (210 kg N ha −1 ) could induce toxicity, resulting in lesser microbial diversity. In addition, CT had lower soil SOC (Li et al, 2010; Liu et al, 2021) and C/N ratio compared with NT (Fiorini et al, 2020), which leads to carbon limiting for microorganisms. Hence, the effect of N application had a smaller effect on microbial diversity under CT than NT.…”
Section: Discussionmentioning
confidence: 99%
“…The observations of positive and quadratic relationships of SOC with root biomass and aboveground biomass, respectively ( Figures 4A, B ) support the above discussion. In addition, less tillage associated with conversion from annual crops (Y0) to perennial mugwort could decrease the fragmentation of soil aggregates and thus decomposition of soil organic matters ( Liu et al., 2021b ; Kan et al., 2022 ; Lessmann et al., 2022 ; Mondal and Chakraborty, 2022 ), which can increase the storage of SOC. Moreover, it has been documented that enzyme activity plays a vital role in regulating organic carbon in agricultural soils and shows a positive relationship with SOC ( Cattaneo et al., 2014 ; Zhang et al., 2021a ).…”
Section: Discussionmentioning
confidence: 99%
“…Regression and path analyses showed that there were indirect impacts of aboveground biomass on SOC through affecting root biomass and thus AG and BG activities (Figures 4, 6). In addition, given the important role of pH in regulating C mineralization (Kemmitt et al, 2006;Zhang et al, 2021b), increased pH associated with decreased soil total N could stimulate soil respiration (C mineralization process) and consequently reduce SOC under long-term mugwort cropping (Figures 1, 3, 6), which is consistent with that found in a recent study (Lu et al, 2022). Irrespective of the temporal impacts of mugwort cropping on SOC, the contributions of C-degrading hydrolytic enzyme activities (i.e., AG and BG) and soil (e.g., TN and TP, Figure 5) were greater than those of biotic factors (aboveground and root biomass) on SOC along the chronosequence cropping.…”
Section: Changes In Soil Properties and Their Impacts On Socmentioning
confidence: 99%
“…In this study, high N application rate (210 kg N ha -1 ) could induce toxicity, resulting in lesser microbial diversity. In addition, CT had lower soil SOC (Liet al , 2010;Liu et al , 2021) and C/N ratio compared with NT (Fiorini et al , 2020), which leads to carbon limiting for microorganisms. Hence, the effect of N application had a smaller effect on microbial diversity under CT than NT.…”
Section: Soil Microbial Diversity and Community Structurementioning
confidence: 99%